Pengaruh Kinerja Keuangan Terhadap Strategi Bisnis PT HM Sampoerna Tbk. Tahun 2023 - Hartono, Ardhit Wiro; Putra, Viko Rachmatullah; Intan, Lusi Reni (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study analyzes the financial performance of PT HM Sampoerna Tbk. in 2023 using financial ratios, including profitability, liquidity, and solvency. The data used originates from the company's annual financial statements. The applied method is descriptive analysis with a quantitative approach, utilizing financial ratios such as Debt to Asset Ratio (DAR), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), Return on Assets (ROA), and Current Ratio. The results of the study indicate that PT HM Sampoerna Tbk. has a stable financial performance, with increased profitability, healthy liquidity, and maintained solvency. These findings have significant implications for strengthening the company's competitiveness in the tobacco industry market.